Upconversion under Photon Trapping in ZnO/BN Nanoarray: An Ultrahigh Responsivity Solar‐Blind Photodetecting Paper (Small 22/2022). Issue 22 (2nd June 2022) - Liu, Guozhen; Chen, Han; Lu, Shiqiang; Liu, Lian; Xu, Xiangyu; Shi, Lan; Chen, Binghuan; Guo, Bin; Shen, Peng; Cai, Yehang; Zhang, Hongye; Tang, Yan; et al.
Abstract : Photodetecting Paper In article number 2200563, Xiaohong Chen, Duanjun Cai, and co‐workers develop a solar‐blind photodetecting paper based on ZnO nanoarray and 2D h‐BN interlayer with ultrahigh responsivity up to 700 A W −1 @ 265–276 nm and switchable detection bands between UVA (>315 nm) and UVC (<280 nm), through up‐conversion absorption and negative differential resistance effect.